Somehow : thoughts on love - Lamott, Anne (Riverhead Books, 2024)
""Love is our only hope," Anne Lamott writes in this perceptive new book. "It is not always the easiest choice, but it is always the right one, the noble path, the way home to safety, no matter how bleak the future looks." In Somehow: Thoughts on Love, Lamott explores the transformative power that love has in our lives: how it surprises us, forces us to confront uncomfortable truths, reminds us of our humanity, and guides us forward. "Love just won't be pinned down," she says. "It is in our very atmosphere" and lies at the heart of who we are. We are, Lamott says, creatures of love. In each chapter of Somehow, Lamott refracts all the colors of the spectrum. She explores the unexpected love for a partner later in life. The bruised (and bruising) love for a child who disappoints, even frightens. The sustaining love among a group of sinners, for a community in transition, in the wider world. The lessons she underscores are that love enlightens as it educates, comforts as it energizes, sustains as it surprises. Somehow is Anne Lamott's twentieth book, and in it she draws from her own life and experience to delineate the intimate and elemental ways that love buttresses us in the face of despair as it galvanizes us to believe that tomorrow will be better than today. Full of the compassion and humanity that have made Lamott beloved by millions of readers, Somehow is classic Anne Lamott: funny, warm, and wise"--